Highly conductive high temperature resistant wire
Patent Information
- Application Number
- CN202521762918.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-19
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2035-08-19
AI Technical Summary
[0004]本实用新型技术方案针对现有技术解决方案过于单一的技术问题,提供了显著不同于现有技术的解决方案,主要提供了一种高导电耐高温导线,用以解决上述背景技术中提出的技术问题
(1)通过设置铜银复合线基材与纳米石墨烯 、氮化钛复合层组成的导体层,利用铜银的高导电性与复合涂层的耐高温抗氧化性形成 “电子 - 声子协同传输通道”,实现高温环境下高导电性能的稳定保持。
Smart Images

Figure CN224851623U_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The utility model mainly relates to the technical field of special wire, concretely to a high-conductivity high-temperature-resistant wire. BACKGROUND
[0002] In the high-end field of new energy vehicles, high-temperature industries, supercomputing centers, etc., as the core carrier of energy and signal transmission, the performance of the wire directly affects the operation efficiency, reliability and service life of the equipment. Currently, these scenes have put forward double strict requirements of "high conductivity" and "high temperature resistance" for the wire: on the one hand, the motor winding and high-current power supply system require the wire to have excellent conductivity to reduce transmission loss and meet the demand of large current (≥200A) transmission; on the other hand, the temperature of the equipment operating environment is often as high as 300℃ or above (such as new energy vehicle motor compartment, industrial furnace periphery), and the wire needs to maintain structural stability and performance consistency under long-term high temperature.
[0003] However, the existing high-conductivity wire mostly relies on pure silver or silver-plated copper conductor, and its conductivity can reach more than 95% of that of pure copper (international annealed copper standard, IACS), but the silver layer is easy to oxidize and peel off at 300℃ or above, resulting in a sharp increase in the resistivity of the conductor, and even causing a circuit break; while the traditional high-temperature-resistant wire often uses nickel-based alloy as the core conductor, which can withstand high temperature of 400℃ or above, but its conductivity is only 15%-20% of that of pure copper, which cannot meet the low-loss requirement of large-current transmission. At the same time, the thermal expansion coefficients of the conductor and the insulating layer are significantly different, and during high-temperature cycling (such as -40℃~400℃), cracks or even peeling may occur at the interface, resulting in insulation failure. Traditional insulation materials (such as mica tape, glass fiber) either have large thickness and poor flexibility, which are difficult to adapt to the complex wiring of precision equipment, or have fast insulation performance degradation under high temperature, and cannot withstand a working environment of 400℃ or above for a long time. Therefore, a special wire with high conductivity (≥85% IACS at 400℃), high temperature resistance (≥400℃), low interfacial thermal stress and high current carrying capacity is proposed. UTILITY MODEL CONTENTS
[0004] The utility model technical scheme provides a solution significantly different from the prior art to solve the technical problem in the prior art, mainly providing a high-conductivity high-temperature-resistant wire to solve the technical problem in the background art.
[0005] The utility model solves the above technical problems by adopting the following technical scheme: A high-conductivity, high-temperature resistant wire includes a conductor layer, a transition layer, an insulation layer arranged sequentially from the inside to the outside, and a heat dissipation structure arranged along the wire axis. The conductor layer includes a copper-silver composite wire substrate and a modified coating. The transition layer is a gradient expansion buffer layer and is wrapped around the outside of the conductor layer. The insulation layer includes an inner insulation layer and an outer insulation layer. The heat dissipation structure includes annular heat dissipation fins arranged at intervals and microchannels embedded in the insulation layer.
[0006] Preferably, the copper-silver composite wire substrate includes a copper core, and the copper core is located inside the silver layer.
[0007] Preferably, the modified coating is a composite layer of nano-graphene and titanium nitride, and the modified coating is laser-fused onto the surface of the copper-silver composite wire substrate.
[0008] Preferably, the transition layer is a mixture of pyrolytic carbon and silicone rubber, and the coefficient of thermal expansion of the transition layer exhibits a gradient transition.
[0009] Preferably, the inner insulating layer is a vapor-deposited alumina ceramic layer with a porosity of less than or equal to %, and the outer insulating layer is a co-extruded layer of polyether ether ketone (PEEK) and silicon carbide whiskers with a silicon carbide content of %.
[0010] Preferably, the annular heat dissipation fins are equidistantly distributed along the axial direction of the conductor, and the annular heat dissipation fins are made of copper-diamond composite material.
[0011] Preferably, the microchannel is filled with a phase change thermally conductive adhesive.
[0012] Compared with the prior art, the beneficial effects of this utility model are as follows: (1) By setting a conductor layer composed of copper-silver composite wire substrate and nano-graphene and titanium nitride composite layer, the high conductivity of copper and silver and the high temperature resistance and oxidation resistance of composite coating are used to form an “electron-phonon synergistic transmission channel” to achieve stable maintenance of high conductivity under high temperature environment.
[0013] (2) By setting a pyrolytic carbon and silicone rubber mixed layer as a transition layer on the outside of the conductor layer, the microporous structure absorbs the interface deformation energy and the thermal expansion coefficient is gradient transition, thereby reducing the stress caused by the difference in thermal expansion coefficient between the conductor layer and the insulation layer, and preventing delamination at high temperature.
[0014] The present invention will be explained in detail below with reference to the accompanying drawings and specific embodiments. Attached Figure Description
[0015] Fig. 1 This is a schematic diagram of the overall structure of this utility model; Fig. 2 This is a schematic diagram of the overall frontal cross-sectional structure of this utility model.
[0016] Numbering on the map: 1. Conductor layer; 101. Copper-silver composite wire substrate; 102. Modified coating; 2. Transition layer; 3. Insulation layer; 301. Inner insulation layer; 302. Outer insulation layer; 4. Heat dissipation structure; 401. Annular heat dissipation fins. Detailed Implementation
[0017] To facilitate understanding of this utility model, a more comprehensive description of the utility model will be given below with reference to the accompanying drawings, which show several embodiments of the utility model. However, the utility model can be implemented in different forms and is not limited to the embodiments described in the text. On the contrary, these embodiments are provided to make the disclosure of the utility model more thorough and comprehensive.
[0018] It should be noted that when an element is referred to as being "fixed to" another element, it can be directly on the other element or there may be an intervening element. When an element is referred to as being "connected to" another element, it can be directly connected to the other element or there may be an intervening element. The terms "vertical," "horizontal," "left," "right," and similar expressions used in this document are for illustrative purposes only.
[0019] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly associated with those skilled in the art to which this invention pertains. The terminology used herein is for the purpose of describing particular embodiments and is not intended to limit the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0020] Please refer to the appendix carefully. Figs. 1-2 A high-conductivity, high-temperature resistant wire includes a conductor layer 1, a transition layer 2, an insulation layer 3 arranged sequentially from the inside to the outside, and a heat dissipation structure 4 arranged along the axial direction of the wire.
[0021] The conductor layer 1 includes a copper-silver composite wire substrate 101 and a modified coating 102. The copper-silver composite wire substrate 101 includes a copper core located inside the silver layer, with the copper core accounting for 80% of the diameter. The surface silver layer is 2μm thick, utilizing the excellent conductivity of pure copper to construct a low-resistance transmission foundation. The 2μm silver layer further reduces the interfacial contact resistance and optimizes current conduction efficiency. The modified coating 102 is a composite layer of nano-graphene and titanium nitride, and is laser-clad onto the surface of the copper-silver composite wire substrate 101. The laser cladding process achieves metallurgical bonding between the coating and the substrate, with a peel strength ≥15MPa. The thickness of the nano-graphene and titanium nitride composite layer is 0.5-1μm. The copper-silver substrate and the modified coating 102 form an "electron-phonon synergistic transmission channel," resulting in a conductivity attenuation rate ≤7% at 400℃. This solves the problem of a sudden increase in resistivity caused by silver layer oxidation at high temperatures in traditional silver-plated wires, achieving stable maintenance of high conductivity under high-temperature conditions.
[0022] The transition layer 2 is a gradient expansion buffer layer wrapped around the outside of the conductor layer 1, with an overall thickness controlled at 0.1 mm. The transition layer 2 is a mixture of pyrolytic carbon and silicone rubber. The pyrolytic carbon and silicone rubber mixture absorbs interfacial deformation energy through the microporous structure with a pore size of 5-10 μm. The thermal expansion coefficient of the transition layer 2 has a gradient transition, thereby gradually matching the performance difference between the conductor layer 1 with a high expansion coefficient and the insulation layer 3 with a low expansion coefficient. Through the gradient transition of the thermal expansion coefficient, the deformation stress during temperature changes is gradually released radially. Combined with the absorption of deformation energy by the microporous structure, the ultra-thin design of 0.1 mm thickness achieves a flexible connection between the conductor layer 1 and the insulation layer 3 without increasing the overall outer diameter of the conductor.
[0023] Insulation layer 3 includes an inner insulation layer 301 and an outer insulation layer 302. The inner insulation layer 301 is a 50μm thick vapor-deposited alumina ceramic layer. The alumina ceramic layer provides basic insulation. The vapor deposition technology ensures that the coating is dense and uniform, without obvious pinholes or cracks, so that the alumina ceramic layer and the surface of the transition layer 2 form a strong bond. The porosity of the inner insulation layer 301 is less than or equal to 3%. The low porosity ≤3% can reduce the voids inside the vapor-deposited alumina ceramic layer, preventing the intrusion of gas, water vapor or corrosive media in high-temperature environments through the pores, thereby reducing the risk of insulation breakdown and ensuring that excellent dielectric properties are maintained even under high-temperature conditions such as 400℃. The outer insulation layer 302 is a 0.3mm thick co-extruded layer of polyetheretherketone (PEEK) and silicon carbide whiskers, with a silicon carbide whisker content of 8%. The silicon carbide whiskers are oriented along the conductor axis, forming a three-dimensional network structure with the PEEK matrix, which retains the PEEK... Its high temperature resistance allows for long-term use at temperatures ≥260℃, and the overall mechanical strength is enhanced by the reinforcing effect of whiskers.
[0024] The heat dissipation structure 4 includes spaced-apart annular heat dissipation fins 401 and microchannels embedded in the insulating layer 3. The microchannels are arranged along the axial direction of the conductor, consistent with the length direction of the conductor, enabling heat conduction and diffusion along the length of the conductor. The annular heat dissipation fins 401 are equidistantly distributed along the axial direction of the conductor, with a spacing of 10mm. The annular heat dissipation fins 401 are made of copper-diamond composite material, with a diamond content of 30%-50%. The microchannels are filled with phase change thermally conductive adhesive, and the cross-sectional dimensions of the microchannels are 0.2×0.2mm². The annular heat dissipation fins 401 increase the heat dissipation area, rapidly transferring heat from inside the conductor to the external environment. The phase change thermally conductive adhesive in the microchannels undergoes a phase change from solid to liquid when the temperature rises, absorbing a large amount of latent heat and transferring the heat to the annular heat dissipation fins 401. The two work together to form "pulse-type heat dissipation," increasing the heat flux density by 3 times.
[0025] The assembly process of a high-conductivity, high-temperature resistant wire is as follows: Preparation and modification of conductor layer 1: Select oxygen-free copper rods with a purity of ≥99.95%, and make copper cores with a diameter ratio of 80% by stretching process. Then, use electroplating process to uniformly coat the surface of copper cores with a 2μm thick silver layer to form copper-silver composite wire substrate 101.
[0026] Modified coating 102 laser cladding: The copper-silver composite wire substrate 101 is fixed on the rotating table of the laser cladding equipment. Powder raw materials are prepared according to the ratio of 3%-5% of nano-graphene and titanium nitride. The mixed powder is clad onto the surface of the substrate by a fiber laser to form a composite coating with a thickness of 0.5-1μm. During the cladding process, the substrate rotation speed is controlled at 500r / min to ensure uniform coating. Finally, the metallurgical bonding with the substrate is achieved with a peel strength ≥15MPa.
[0027] Transition layer 2 coating: Pyrolytic carbon powder and silicone rubber matrix are mixed at a mass ratio of 7:3, and an appropriate amount of solvent is added to make a paste. The paste is then pressed into a 0.1 mm thick sheet using a mold, with a 5-10 μm microporous structure reserved (achieved by removing the pore-forming agent later). Conductor layer 1 is passed through a special coating equipment, and the mixed material sheet is spirally wound around the outside of conductor layer 1. The winding tension is controlled at 5-10 N to ensure a tight fit. Then, it is cured in an oven at 150°C for 2 hours to form transition layer 2, where the coefficient of thermal expansion gradients from close to the copper-silver conductor on the inside to close to the insulating layer 3 on the outside.
[0028] Insulation layer 3 forming: The wire covered with transition layer 2 is placed in a chemical vapor deposition (CVD) device, and a 50 μm thick alumina ceramic layer is deposited under certain conditions. The porosity is ensured to be ≤3% by controlling the deposition rate to 1 μm / min. Polyether ether ketone (PEEK) particles are mixed with 8% silicon carbide whiskers and fed into a twin-screw extruder. After melt blending at 380°C, the mixture is extruded through a die to cover the outside of the inner insulation layer 301, forming an outer insulation layer 302 with a thickness of 0.3 mm. During the extrusion process, the traction speed and the wire advance speed are controlled to ensure that the whiskers are oriented along the axial direction.
[0029] Heat dissipation structure 4 integration: During the extrusion process of the outer insulation layer 302, an axial channel with a cross section of 0.2×0.2mm² is reserved inside the outer insulation layer 302 through the micro-conduit embedded in the mold. After cooling and solidification, the conduit is extracted to form a microchannel. Then, phase change thermally conductive adhesive is filled into the microchannel through the glue injection equipment and the port is sealed. The copper-diamond composite material is processed into annular fins with a thickness of 0.5mm and an outer diameter 1mm larger than that of the outer insulation layer 302. The fins are then welded to the surface of the outer insulation layer 302 at equal intervals of 10mm along the axial direction of the conductor using laser welding power of 200W. The diameter of the welding point is ≤0.3mm, ensuring a tight bond with the insulation layer 3 without damaging the internal structure.
[0030] The present invention has been described above by way of example in conjunction with the accompanying drawings. Obviously, the specific implementation of the present invention is not limited to the above-described manner. Any non-substantial improvement made by adopting the inventive concept and technical solution of the present invention, or the direct application of the inventive concept and technical solution of the present invention to other occasions without modification, shall be within the protection scope of the present invention.
Claims
1. A high-conductivity, high-temperature resistant wire, characterized in that: It includes a conductor layer (1), a transition layer (2) and an insulating layer (3) arranged sequentially from the inside to the outside, as well as a heat dissipation structure (4) arranged along the conductor axis; The conductor layer (1) includes a copper-silver composite wire substrate (101) and a modified coating (102) covering the outer surface of the copper-silver composite wire substrate (101). The copper-silver composite wire substrate (101) includes a copper core and a silver layer covering the outside of the copper core. The transition layer (2) is wrapped around the outside of the conductor layer (1), and the transition layer (2) is a gradient expansion buffer layer with a microporous structure; The insulating layer (3) includes an inner insulating layer (301) and an outer insulating layer (302). The inner insulating layer (301) is wrapped around the outside of the transition layer (2), and the outer insulating layer (302) is wrapped around the outside of the inner insulating layer (301). The heat dissipation structure (4) includes annular heat dissipation fins (401) spaced along the conductor axis on the outside of the outer insulation layer (302), and microchannels extending along the conductor axis and embedded in the outer insulation layer (302).
2. The high conductivity and high temperature resistant wire according to claim 1, characterized in that: The diameter of the copper core is 80% of the diameter of the copper-silver composite wire substrate (101), and the silver layer covers the outside of the copper core with a thickness of 2μm.
3. The high conductivity and high temperature resistant wire according to claim 1, characterized in that: The thickness of the modified coating (102) is 0.5 to 1 μm.
4. The high conductivity and high temperature resistant wire according to claim 1, characterized in that: The thickness of the transition layer (2) is 0.1 mm, and the pore size of the microporous structure is 5 to 10 μm.
5. The high conductivity and high temperature resistant wire according to claim 1, characterized in that: The thickness of the inner insulating layer (301) is 50 μm, and the thickness of the outer insulating layer (302) is 0.3 mm.
6. The high conductivity and high temperature resistant wire according to claim 1, characterized in that: The annular heat dissipation fins (401) are equidistantly distributed along the axial direction of the conductor, and the spacing between adjacent annular heat dissipation fins (401) is 10mm.
7. The high conductivity and high temperature resistant wire according to claim 1, characterized in that: The microchannel has a cross-sectional dimension of 0.2×0.2mm², is filled with phase change thermally conductive adhesive, and has sealed ports.